HUBUNGAN POLA KOMUNIKASI DENGAN KEJADIAN TEMPER TANTRUM PADA ANAK USIA PRA SEKOLAH DI TK ISLAMIC CENTER MANADO - Yiw’Wiyouf, Rosa Maria Suwarni; Ismanto, Amatus Yudi; Babakal, Abram (Universitas Sam Ratulangi, 2017)
Abstract : Temper tantrums are an explosion of anger that often occurs in children aged zero to six years expressed by crying, screaming, throwing, rolling, punching, and other destructive activities. The pattern of effective communication is one of the appropriate remedial action in reducing the incidence of temper tantrums in children of preschool age. The Purpose is to knowing the relationship between the pattern of effective communication with the incidence of temper tantrums at pre-school age children in kindergarten Islamic Center Manado. The method is cross-sectional and used questionnaires to obtain data from respondents. The Sampling technique is purposive sampling with 30 respondents. The Results using Chi-Square obtained p-value of 0.000 (α = 0.05). The Conclusion shows there is a relationship patterns of communication with the incidence of temper tantrums in preschool children in Nursery Islamic Center Manado. Keywords: Communication Pattern, Temper Tantrums, Pre-School Age Abstrak : Temper tantrum adalah suatu ledakan amarah yang sering terjadi pada anak usia nol sampai 6 tahun yang diungkapkan dengan menangis, menjerit, melempar benda, berguling-guling, memukul, dan aktifitas destruktif lainnya. Pola komunikasi efektif adalah salah satu tindakan penanganan yang tepat dalam mengurangi kejadian temper tantrum pada anak usia pra sekolah. Tujuan mengetahui hubungan antara pola komunikasi orang tua dengan kejadian temper tantrum pada anak usia pra sekolah di TK Islamic Center Manado. Metode Penelitian yaitu cross sectional study dan menggunakan kuesioner untuk mendapatkan data dari responden. Teknik pengambilan sampel pada penelitian ini yaitu purposive sampling dengan jumlah sampel 30 responden. Hasil Penelitian menggunakan uji Chi-Square di dapat p-value sebesar 0,000 (α= 0,05). Kesimpulan menunjukan adanya hubungan pola komunikasi orang tua dengan kejadian temper tantrum pada anak usia pra sekolah di Tk Islamic Center Manado. Kata kunci : Temper Tantrum, Pola Komunikasi, Anak Usia Pra Sekolah